Copper And Zinc Mining Tailings as A Partial Replacement for Cement to Increase the Compressive Strength of Concrete - Vallejos, Carlos Magno Chavarry; Rodríguez, Joaquín Samuel Támara; Reyes, Liliana Janet Chavarría; Serrano, Jackeline Carol Escobar; Lindo, Marco Antonio Silva; Giraldo, Russell Darcy Leyva; Huerta, David Minaya; González, Carla Grisselle Poma (International Journal of Membrane Science and Technology, 2023)
This study uses copper and zinc mining waste from mining activity as a partial substitute for cement in the concrete mix. This initiative seeks to strengthen the compressive strength of concrete. Copper and zinc waste can partially replace the cement content in concrete due to meeting the necessary physical and chemical requirements. In addition, these residues promote the formation of binders that improve the hydration of Portland cement. This approach improves the physical and mechanical properties of concrete and its durability. It also has economic and environmental advantages, as it uses copper and zinc waste from mining operations. Obtaining copper involves processing minerals from mines, which may contain copper oxides or sulfides. The rock is milled to obtain copper and zinc; these elements are separated using water, air, and other chemicals. The resulting by-products are stored in mining waste deposits that comply with current regulations. As for the research methodology, a deductive approach with applied orientation and a quantitative approach is followed. A retroactive data collection instrument is used to describe and explain the process. The optimal percentage of joint incorporation of copper and zinc residues from mining activity is around 10% and 5%, respectively. If you want to use only copper waste, you could reach up to 30%, while zinc waste can be incorporated in a maximum of 5%. In addition, it is observed that incorporating lead and zinc residues by 40% instead of cement increases compressive strength by 18%.